2012
DOI: 10.1080/14999013.2012.746759
|View full text |Cite
|
Sign up to set email alerts
|

Explicating the Construct of Psychopathy: Development and Validation of a Conceptual Model, the Comprehensive Assessment of Psychopathic Personality (CAPP)

Abstract: Psychopathic personality disorder (PPD) has important clinical and forensic implications. But much more effort has been devoted to assessing or diagnosing PPD than to explicating or defining it. In the first part of this paper, we describe the development of a conceptual model or "concept map" of PPD. Based on a systematic review of descriptions of PPD in the clinical and research literature, as well as consultation with subject matter experts, we identified key features of the disorder and translated them int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
219
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(232 citation statements)
references
References 42 publications
(44 reference statements)
7
219
0
6
Order By: Relevance
“…Based on these findings, Gatner et al suggested that Boldness appears to be more of a marker of positive adjustment and does not appear to be essential to the definition of psychopathic personality disorder. Gatner, Douglas, and Hart (2017) compared the lexical similarity of the triarchic model of psychopathy to two contemporary models of psychopathy, i.e., the Comprehensive Assessment of Psychopathic Personality (CAPP; Cooke, Hart, Logan, & Michie, 2012), and the Five Factor Model of psychopathy (FFM; Widiger & Lynam, 1998). Lexical similarity indicated the similarity in meaning or definition between two terms or words.…”
Section: Limitations and Questions Regarding Validity Of The Tripmmentioning
confidence: 99%
“…Based on these findings, Gatner et al suggested that Boldness appears to be more of a marker of positive adjustment and does not appear to be essential to the definition of psychopathic personality disorder. Gatner, Douglas, and Hart (2017) compared the lexical similarity of the triarchic model of psychopathy to two contemporary models of psychopathy, i.e., the Comprehensive Assessment of Psychopathic Personality (CAPP; Cooke, Hart, Logan, & Michie, 2012), and the Five Factor Model of psychopathy (FFM; Widiger & Lynam, 1998). Lexical similarity indicated the similarity in meaning or definition between two terms or words.…”
Section: Limitations and Questions Regarding Validity Of The Tripmmentioning
confidence: 99%
“…estos resultados avivan el debate sobre el sistema de evaluación utilizado para la psicopatía en el interior de las prisiones. tal y como señalan garrido (2004) y otros autores (cooke et al, 2012;Patrick et al, 2009;Pérez et al, 2015;pozueco, 2010), en las prisiones se localizan individuos que, aunque mantienen una personalidad psicopática, pasan desapercibidos para el sistema penitenciario por no cumplir los criterios de conducta antisocial adscritos al pcl-r, instrumento más utilizado para su evaluación en prisiones. Desde una perspectiva práctica, si bien el mantenimiento de esta alta exigencia para establecer la presencia de psicopatía (además de presentar una personalidad psicopática, deben presentar una carrera criminal) permite que los prejuicios y dificultades asociadas a este etiquetamiento se limiten a aquellos que tienen un cuadro de mayor complejidad, lo cierto es que sesga nuestra comprensión del constructo y perjudica el trabajo realizado por los profesionales de los establecimientos penitenciarios.…”
Section: Discussionunclassified
“…esta situación, para parte de los estudiosos sobre el tema, es considerada como sintomatológica de un cuadro clínico a reflejar desviación personal, no desviación social o cultural (Andrade, 2008;Cooke, Hart, Logan y Michie, 2012;Cooke, Michie, Hart y Clark, 2004;Skeem y Cooke, 2010;Vinet, 2010). Fruto de ello es el desarrollo de la estructura factorial jerárquica de 3 factores para PCL-R a manos de Cooke y sus colegas (Cooke y Michie, 2001; cooke, Michie y skeem, 2007), que implica suprimir los ítems sobre conducta antisocial.…”
Section: Perfil Del Psicópata Institucionalizado Sin Comportamiento Cunclassified
“…Problemem tym w ostatnich latach zajmowali się głównie Robert D. Hare (2003Hare ( , 2010, Ronald Blackburn (1998aBlackburn ( , 1998bBlackburn ( , 2005, Theodore Millon (1998) oraz David J. Cooke (2012), a na gruncie polskim Kazimierz Pospiszyl (2000), Beata Pastwa-Wojciechowska (2004) oraz Józef K. Gierowski (2007Gierowski ( , 2012. Zarówno w populacji ogólnej, jak i wśród osób wchodzących w konflikt z prawem, psychopatia diagnozowana jest zdecydowanie częściej u mężczyzn (Grann 2000; Pastwa-Wojciechowska 2011).…”
Section: Wprowadzenieunclassified